Analisis Pengaruh Pengembangan Kepemimpinan, Pembinaan, Pelatihan Dan Pengembangan, Pemberdayaan, Partisipasi Terhadap Kinerja Karyawan Pada Perusahaan Manufaktur Di Batamindo - Zunara, Nita; Fatyandri, Adi Neka (Universitas Pelita Harapan Medan, 2017)
The purpose of this research is to analize the impact between leadership development, coaching, training and development,empowerment,participation to employee performance. This research done at industries company in Batam. this research used 300 respondent which is manufactur companies’ staff in Batamindo. The method we used in choosing sample is nonprofitable method. This study analyzes the demographic factors of gender, age, education, past work and the company name. The statistical method used to test the hypothesis is multiple linear regression and tools used are program Statistical Package for Social Science (SPSS). The Results from the study showed that leadership development, coaching, training and development, empowerment, participation significantly affect the performance of employees at the company Manufacturing.Keywords: Leadership development, coaching, training and development, employee empowerment, participation, employee performance.